Ethnobotanical survey of medicinal plants used by the Punan people of Sarawak, Borneo: a conservation perspective - Rajoo, Keeren Sundara; Lepun, Philip; Kayok, Beatrice Lyeja Anak; Hakiman, Mansor; Irie, Mami (SAGE Publications, 2025)
Background and Research Aims: The Punan people of Sarawak, Borneo, possess rich traditional medicinal knowledge, but face threats to their cultural heritage and local biodiversity. This study aimed to document the diversity of medicinal plants used by the Punan, assess their conservation status, and propose evidence-based conservation strategies. Methods: Ethnobotanical surveys were conducted in two Punan longhouses in Tatau, Sarawak. Structured and semi-structured interviews were used to collect data from 13 knowledgeable individuals. Plant species were identified with the help of dendrologists and confirmed using online botanical databases. Quantitative ethnobotanical indices were calculated, and conservation statuses were assessed using the IUCN Red List. Results: The study documented 19 plant species from 17 families used for medicinal purposes. Senna alata, Elephantopus scaber, and Mimosa pudica had the highest use-reports. Respiratory, eye, and skin ailments were the most frequently treated conditions. Two species of conservation concern were identified: Cissus rostrata (regionally Critically Endangered) and Coscinium fenestratum (Vulnerable). Conclusion: This study revealed a rich traditional pharmacopoeia among the Punan people, while also highlighting critical conservation concerns for certain medicinal plant species. The findings underscore the urgent need for integrated conservation approaches that address both ecological and cultural dimension. Implications for Conservation: Conservation strategies should prioritize protection of vulnerable species through sustainable harvesting practices, habitat protection, and ex situ conservation measures. Community engagement is crucial, involving the establishment of community-managed medicinal plant reserves and sustainable livelihood opportunities. These efforts will contribute to both ecological sustainability and cultural resilience in the region.